Pelaksanaan Pendidikan Karakter Siswa Kelas IV Madrasah Ibtidaiyah Darul Ulum Pekanbaru - Fadilla, Dewi; Siti Quratul Ain (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2023)
The aim of this research is to describe the implementation of character education for class IV students at MI Darul Ulum Pekanbaru. Apart from that, it describes the inhibiting factors that influence the implementation of character education for class IV students at MI Darul Ulum Pekanbaru. The research method used is a qualitative approach, namely research from an inductive perspective, which relies on participatory item perceptions of social characteristics. Data validity using triangulation. The data analysis technique applied, namely the Miles and Huberman Model, was used. The research results obtained are that the implementation of student character education has been carried out by teachers and schools through three processes, namely: the process of teaching and learning activities (KBM), the process of extracurricular activities, the process of habituation through school culture. Meanwhile, the inhibiting factors that influence the implementation of character education for class IV students are firstly the awareness of students who are of primary school/madrasah age, students tend to like to play. Second, limited school control and third, school communication with students' parents.